1995
DOI: 10.1128/aac.39.2.559
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of suture and cyanoacrylate tissue adhesive on bacterial counts in contaminated lacerations

Abstract: We studied the effects of closing lacerations with suture or cyanoacrylate tissue adhesive on staphylococcal counts in inoculated guinea pig lacerations. Wounds closed with adhesive alone had lower counts than wounds containing suture material (P <0.05). The results of a time-kill study were consistent with a bacteriostatic adhesive effect of the adhesive against Staphylococcus aureus.Cyanoacrylate tissue adhesive is an organic polymer that effectively closes simple lacerations in humans and animals (1,7,9). H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 10 publications
3
27
0
3
Order By: Relevance
“…8,12,13 A recent study by Davis et al 11 reports the faster healing of partial thickness wounds using a 2-octyl cyanoacrylate formulation.…”
Section: Sommairementioning
confidence: 98%
“…8,12,13 A recent study by Davis et al 11 reports the faster healing of partial thickness wounds using a 2-octyl cyanoacrylate formulation.…”
Section: Sommairementioning
confidence: 98%
“…They concluded that contaminated wounds closed with sutures had higher infection rates compared with those reported with topical tissue adhesive. Howell et al [22] studied the effects of closing lacerations with suture or cyanoacrylate tissue adhesive on staphylococcal counts in inoculated guinea pig lacerations. Wounds closed with adhesive alone had lower counts than wounds containing suture material.…”
Section: Discussionmentioning
confidence: 99%
“…( J AAPOS 2012;16: 168-172) I n previous studies authors have documented the benefits of wound closure with tissue adhesives compared with sutured wound closure. [1][2][3][4][5][6][7] The purpose of this report is to describe cases of periorbital cellulitis after wound closure of traumatic periorbital lacerations with 2-octyl cyanoacrylate (Dermabond; Ethicon, Inc, Somerville, NJ) and to evaluate the existing literature to identify a trend toward an increased infection rate with tissue adhesive closure.…”
Section: Discussionmentioning
confidence: 99%